A broken sculpture of Lord Surya - Temples of India Project Team (Jio Institute, 2024)
This is a broken sculpture of Surya with two lotuses in his upper hands. There are several loose sculptures placed on pedestals, on the ground floor of the matha (monastic or residential building) of the Mahanaleshwar temple complex. These fragments were collected by the Archaeological Survey of India (ASI) within the Mahanaleshwar temple complex.